Doing Quantitative Psychological Research / From Design to Report - Clark-Carter David (Psychology Press, Ltd, 1997)
Preface, Introduction, The Methods Used in Psychological Research, The Preliminary Stages of Research, Variables and the Validity of Research Designs, Research Designs and their Internal Validity, Asking Questions I: Interviews and Surveys, Asking Questions II: Measuring Attitudes and Meaning, Observation and Content Analysis, Scales of Measurement, Summarising and Describing Data, Going Beyond Description, Samples and Populations, Analysis of Differences between a Single Sample and a Population, Effect Size and Power, Parametric and Non-Parametric tests, Subsequent Analysis after ANOVA or (S{(B2, Analysis of Relationships I: Correlation, Analysis of Relationships I: Correlation, Analysis of Relationships II: Regression, Multivariate Analyses, Meta-Analysis, Repoting Research.s